Peningkatan Prestasi Belajar Agama Hindu SMP Melalui Model Pembelajaran Ekspositori - Sukardi, Ni Made (Universitas Pendidikan Ganesha, 2018)
This research was carried out at SMP Negeri 3 Sawan in Class VII A8 whose students' ability to materialize Hinduism was low. The purpose of this class action research writing is to find out whether the Expository learning model can improve student learning achievement. The data collection method is a learning achievement test. The data analysis method is quantitative descriptive. The results obtained from this study are Expository can improve student learning achievement. This is evident from the results obtained initially with an average value of 68.71, in the first cycle to 6.49 and in the second cycle to 6.88. The conclusion derived from this study is that the Expository learning model can improve learning achievement.